Remarkable electronic and optical anisotropy of layered 1T’-WTe2 2D materials - Zhang, Qiankun; Zhang, Rongjie; Chen, Jiancui; Shen, Wanfu; An, Chunhua; Hu, Xiaodong; Dong, Mingli; Liu, Jing; Zhu, Lianqing (Beilstein Journal of Nanotechnology, 2019)
Anisotropic 2D materials exhibit novel optical, electrical and thermoelectric properties that open possibilities for a great variety of angle-dependent devices. Recently, quantitative research on 1T’-WTe2 has been reported, revealing its fascinating physical properties such as non-saturating magnetoresistance, highly anisotropic crystalline structure and anisotropic optical/electrical response. Especially for its anisotropic properties, surging research interest devoted solely to understanding its structural and optical properties has been undertaken. Here we report quantitative, comprehensive work on the highly anisotropic, optical, electrical and optoelectronic properties of few-layer 1T’-WTe2 by azimuth-dependent reflectance difference microscopy, DC conductance measurements, as well as polarization-resolved and wavelength-dependent optoelectrical measurements. The electrical conductance anisotropic ratio is found to ≈103 for a thin 1T’-WTe2 film, while the optoelectronic anisotropic ratio is around 300 for this material. The polarization dependence of the photo-response is ascribed to the unique anisotropic in-plane crystal structure, consistent with the optical absorption anisotropy results. In general, 1T’-WTe2, with its highly anisotropic electrical and photoresponsivity reported here, demonstrates a route to exploit the intrinsic anisotropy of 2D materials and the possibility to open up new ways for applications of 2D materials for light polarization detection.
Keywords: 1T’-WTe2; 2D material; anisotropic; light polarization; optoelectrical